Tomato SlWRKY3 acts as a positive regulator for resistance against the root-knot nematode Meloidogyne javanica by activating lipids and hormone-mediated defense-signaling pathways - Chinnapandi, Bharathiraja (Plant Signal Behav, 2019)
Diseases caused by plant-parasitic nematodes in vegetables, among them Meloidogyne spp. root-knot nematodes (RKNs), lead to extensive yield decline. A molecular understanding of the mechanisms underlying plants’ innate resistance may enable developing safe alternatives to harmful chemical nematicides in controlling RKNs. A tight relationship has been revealed between the WRKY transcription factors and RKN parasitism on tomato roots. We investigated the function role of tomato SlWRK3 and SlWRKY35 in regulating nematode disease development. Using promoter–GUS reporter gene fusions, we show that both SlWRKY3 and SlWRKY35 are induced within 5 days of infection and through feeding-site development and gall maturation, with a much stronger response of the former vs. the latter to nematode infection. Histological analysis of nematode-feeding sites indicated a high expression of SlWRKY3 in developing and mature feeding cells and associated vasculature cells, whereas SlWRKY35 expression was only observed in mature feeding sites. Both SlWRKY3 and SlWRKY35 promoters were induced by the defense phytohormones salicylic acid and indole-3-butyric acid, with no response to either jasmonic acid or methyl jasmonate. SlWRKY3 overexpression resulted in lower infection of the RKN Meloidogyne javanica, whereas knocking down SlWRKY3 resulted in increased infection. Phytohormone and oxylipin profiles determined by LC–MS/MS showed that the enhanced resistance in the former is coupled with an increased accumulation of defense molecules from the shikimate and oxylipin pathways. Our results pinpoint SlWRKY3 as a positive regulator of induced resistance in response to nematode invasion and infection, mostly during the early stages of nematode infection.